Factors Influenced the Administration of Colostrum among Mothers with Post-Sectio Caesarean in Bunda Thamrin Hospital, Medan - Etti Sudaryati; Komala Kartikasari Nst Nst; evawany Y Aritonang (International Journal of Nursing and Health Services (IJNHS), 2021)
Colostrum is milk that is secreted by the breast of the mother first after giving birth. This study aimed to analyze the factors that influenced the administration of colostrum among mothers with a post-sectio cesarean. An analytic survey with a cross-sectional design was applied in this study. The data analysis method used in this study uses a multiple logistic regression statistical test. The population in this study were all postpartum mothers who had birth by cesarean sectio procedure. One hundred samples were selected by accidental sampling technique. The results showed that the administration of colostrum among mothers with post sectio cesarean were 75%, The initiation of breastfeeding was 62%, of them have lack knowledge, the support of majority husbands is more petite that is 82%, the role of the majority of health workers is less by 51%. Multivariate test results obtained the probability of a husband's support variable (p = 0.0001) and the role of health workers (p = 0.038) likely to cause post-section cesarean mothers not to give colostrum by 96 percent, while 4 percent is due to other factors